Country Partnership Framework for the Independent State of Papua New Guinea for the Period FY19-FY23 - World Bank Group (World Bank, Washington, DC, 2019)
Papua New Guinea (PNG) is a richly diverse society undergoing intense economic and social transformation. With more than eight hundred different languages spoken among a population of over eight million people, divided into more than one thousand ethnic clans, PNG is the most heterogenous country in the world. The World Bank Group’s (WBG’s) country partnership framework (CPF) for the Independent State of Papua New Guinea for FY19–FY23 is anchored in the government’s Vision 2050, the PNG development strategic plan 2010–2030, and the third medium-term development plan for 2018–2022 (MTDPIII). To support the government in achieving the twin goals, the CPF envisages supporting the government of PNG in pursuing sustainable and inclusive growth and building resilience to shocks across three strategic focus areas: (i) improving macro and fiscal resilience; (ii) ensuring more effective and inclusive service delivery, particularly in underserved areas; and (iii) enabling private sector development and inclusive growth in non-resource sectors. Addressing governance and institutional challenges will be a cross-cutting theme to the program. Close collaboration between the World Bank, the International Finance Corporation (IFC), and the Multilateral Investment Guarantee Agency (MIGA) will be emphasized, with a particular focus on strengthening the business environment and job creation in PNG.